A Narrative Review of Nutritional Therapy for Gastrointestinal Cancer Patients Underwent Surgery. Issue 1 (31st December 2023) - Zhang, Yujie; Zhang, Jinglin; Zhu, Lili; Hao, Jiaqi; He, Fengjun; Xu, Tao; Wang, Rui; Zhuang, Wen; Wang, Mojin
Abstract: Background: Patients with gastrointestinal cancer often suffer from malnutrition during tumor progression. Malnutrition is associated with postoperative complications and decreased quality of life. Supporting cancer patients with proper nutrition is vital for improving their prognoses. Method: Google scholar and PubMed database searches were performed. Selection criteria included gastrointestinal cancer, surgery, ω − 3 fatty acids, randomized clinical trials from 2007 to August 2022. Conclusion: Nutritional therapy includes nutritional counseling, enteral nutrition, parenteral nutrition, and oral nutritional supplements. Immune nutrients like glutamine and ω-3 fatty acid have been demonstrated with benefits in reducing inflammatory responses and postoperative complications, regulating immune function and improving prognosis.